ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ANEMIA PADA IBU HAMIL - Lestari, Dwi; Noviana, Ekki; Safrina, Safrina; Sriwahyuni, Sriwahyuni (Ensiklopedia of Journal, 2025)
Abstract: Anemia during pregnancy is a health problem that requires serious attention and appropriate treatment. Preliminary studies conducted by researchers at the Kintamani Health Center in June 2024 showed 75 pregnant women were recorded as having anemia. The purpose of the study was to determine the factors associated with the incidence of anemia in pregnant women. The research design used in this study was cross sectional. The research was conducted at the Kintamani Health Center. The research was conducted in July 2024. The population is all mothers who are in the working area of the Kintamani VI Health Center. The population size was 196 people. The sample amounted to 73 people. The sampling technique used in this study was Probability Sampling by Systematic Random Sampling. Data analysis was done univariate and bivariate. The results showed a relationship between maternal age (p value: 0.001) and gestational age (p value: 0.001) to the incidence of anemia in pregnant women. It is recommended for the Puskesmas to be more active in providing health education related to the factors that cause anemia in pregnant women and for pregnant women to be able to increase the consumption of nutritious food.Keywords: Anemia, Pregnant Women, Age